Selection and Incorporation of siRNA Carrying Non-Viral Vector for Sustained Delivery from Gellan Gum Hydrogels - Anastasios Nalbadis; Marie-Luise Trutschel; Henrike Lucas; Jana Luetzkendorf; Annette Meister; Karsten Mäder (MDPI AG, 2021)
The local controlled release of siRNA is an attractive and rational strategy to enhance and extend the effectiveness of gene therapy. Since naked and unmodified siRNA has a limited cell uptake and knockdown efficiency, the complexation of siRNA with non-viral carriers is often necessary for the delivery of bioactive RNA. We evaluated the performance of three different non-viral siRNA carriers, including DOTAP lipoplexes (DL), chitosan polyplexes (CP), and solid lipid complexes (SLC). The physicochemical properties of the siRNA-nanocarriers were characterized by dynamic light scattering and gel electrophoresis. After in vitro characterization, the carrier with the most appropriate properties was found to be the DL suspension, which was subsequently loaded into a gellan gum hydrogel matrix and examined for its drug load, stability, and homogeneity. The hydrogels microstructure was investigated by rheology to assess the impact of the rheological properties on the release of the siRNA nanocarriers. A controlled release of complexed siRNA over 60 days in vitro was observed. By comparing the results from fluorescence imaging with data received from HPLC measurements, fluorescence imaging was found to be an appropriate tool to measure the release of siRNA complexes. Finally, the bioactivity of the siRNA released from hydrogel was tested and compared to free DL for its ability to knockdown the GFP expression in a DLD1 colon cancer cell model. The results indicate controlled release properties and activity of the released siRNA. In conclusion, the developed formulation is a promising system to provide local controlled release of siRNA over several weeks.